Bjerke_et_al_Nord_J_Bot_2018_Fig_6 - Bjerke, Jarle; Wierzbinski, Grzegorz; Tømmervik, Hans; Phoenix, Gareth; Bokhorst, Stef (Dryad Digital Repository, 2018)
Number of remaining wintergreen leaves per shoot, and number of new side branches per shoot from snowmelt in early May to early autumn in late August 2016. DOY = day of year.